"Energy" drinks: Help, harm or hype? - Bonci, L. (Sports Science Exchange, 2002)
Many products marketed as energy drinks contain high concentrations of carbohydrate and some caffeine. Some energy drinks contain herbs, amino acids, protein, and other substances, usually in such small amounts that they are unlikely to have any noticeable effect on performance. The content of some of these products may result in inefficient absorption of fluid and nutrients from the intestine, with the possibility of gastrointestinal distress. Many energy drinks are quite costly and, because of their composition, are not suitable for use by athletes. Athletes should be educated about these products and guided towards other foods and fluids that will not pose potential risks.